Diurnal activity budget, stereotypic behaviour and response to enrichment of captive malayan sun bears (Helarctos Malayanus R.) - Tan, Hwee Mien (2010)
The knowledge of an animal's behaviour is important in the assessment of both health and ecological requirements. In captivity, the confined environment and daily management are often considered as crucial factors affecting an animal's behaviour, especially the development of stereotypies. The current study was conducted to document the diurnal activity patterns and stereotypic behaviours in captive Malayan Sun Bear (Helarctos malayanus), to investigate the effect of enclosure design on the stereotypies observed, and to ascertain if environmental enrichment is able to alleviate stereotypic behaviours. A 14-day behavioural observation was carried out on 17 adult H. malayanus which were either housed in groups of four or five in outdoor enclosures, or in pairs in barren indoor enclosures. The diurnal activity budgets of the bears were dominated by resting (Zoo-A: indoor = 22.8 ± 14.8%, outdoor = 58.3 ± 15.6%; Zoo-B: indoor = 25.7 ± 11.0%, outdoor = 52.0 ± 20.1%) and locomotion (Zoo-A: indoor = 44.0 ± 18.7%, outdoor = 28.4 ± 14.2%; Zoo-B: indoor = 36.2 ± 12.3%, outdoor = 23.1 ± 13.5%). All bears in this study performed at least one form of stereotypic behaviour, where pacing was the most common form. When comparison was made between the bears housed indoors and those outdoors, the outdoor bears spent significantly more time resting while the indoor bears displayed higher frequency of locomotion, conspecific interaction as well as total stereotypy. Following baseline data collection, coconut fronds and plastic containers with twigs were then provided as enrichment to the bears for the next 14 days. The enrichment items were then withdrawn over a subsequent 14-day period. Saliva and faeces of the bears were collected for quantification of cortisol hormone. Behavioural and cortisol data were statistically compared between pre-, per- and post-enrichment periods. The enrichment successfully reduced the time spent resting and promoted play behaviour in all groups of bears. However, significant reduction in stereotypic frequency was only observed in the bears housed indoors. The enrichment did not exert a reducing effect on the cortisol in the saliva or faeces.The present study has revealed that enclosure design has a significant effect on the behaviour and manifestation of stereotypies in captive bears. The response of the bears to the enrichment varied between those housed in enriched outdoor enclosures and those in barren indoor enclosures, where reduction in the frequency of stereotypy was only found in the latter. It is therefore necessary that efforts in ex situ conservation of H. malayanus must first address the basic management issues and fulfill the primary requirements of the animals. Environmental enrichment using basic materials is an effective tool to alleviate behavioural anomalies especially where the captive environment is compromised.